The Glu298Asp polymorphism of the NOS 3 gene as a determinant of the baseline production of nitric oxide - Veldman, Bart A; Spiering, Wilko; Doevendans, Peter A; Vervoort, Gerald; Kroon, Abraham A; de Leeuw, Peter W; Smits, Paul (Journal of hypertension, 2002)
The endothelial nitric oxide synthase Glu298Asp polymorphism has been suggested to play a role in the development of hypertension, atherosclerosis and coronary artery disease. To investigate functional differences between the various genotypes with respect to basal nitric oxide (NO) production, we estimated the response to endothelial NO synthase (ecNOS) inhibition by infusion of increasing doses of N(G)-monomethyl-L-arginine (L-NMMA) into the brachial artery during venous occlusion plethysmography. In 41 healthy subjects forearm blood flow responses to intra-arterial infusion of increasing doses of L-NMMA (0.05, 0.1 and 0.2 mg/min per dl) and norepinephrine (10, 20 and 40 ng/min per dl) were measured. The genotype of the ecNOS Glu298Asp polymorphism was assessed. Nineteen subjects had the Glu/Glu genotype, 19 subjects had the Glu/Asp genotype and three subjects had the Asp/Asp genotype. Groups were comparable concerning demographic, hemodynamic and possible confounding factors. Subjects with the Asp allele showed a reduced response to infusion of L-NMMA as compared to subjects with the Glu/Glu genotype (ANOVA, = 0.01). There was no significant difference in the response to infusion of the NO-independent vasoconstrictor, norepinephrine, between both groups. The ecNOS Glu298Asp polymorphism is associated with reduced basal NO production and might therefore have functional implications in the development of atherosclerosis or hypertension.